Strategi Meningkatkan Motivasi Murid dalam Pembelajaran Tahfidz di MI-Al Mukhlashin - Evelin, Farrel; Erianti, Nagita; Arum, Shaka; Ramadhani, Dian; Utami, Amira; Wulandari, Ayu (putrapublisher.org, 2024)
The Qur'an is a guide to human life, and learning Tahfidz is an important means to foster students' love for it. This study aims to reveal effective strategies to increase the motivation to learn Tahfidz of MI Al-Mukhlashin students. Using a qualitative approach, data were collected through participatory observation, in-depth interviews with teachers, principals, and students, as well as documentation studies in the form of learning records and student achievements. The primary data source used Madrasah Ibtidaiyah teachers and principals. The results showed that several strategies proved effective. First, the application of varied learning methods, such as group recitation and the use of audio media, proved to be able to overcome boredom and increase students' understanding of the Qur'an. The use of methods tailored to students' learning styles is also an important factor. Second, a structured and fair reward system, whether in the form of praise, prizes, or certificates, has a positive influence and motivates students to continue to excel in memorizing. This system also needs to be combined with a healthy competition system between students, so as to foster enthusiasm for learning and motivate each other. Third, the active role of parents as the main supporters of Tahfidz learning at home is very significant. Interview results show that parental support in the form of mentoring, creating a conducive learning environment, and providing spiritual motivation contribute greatly to student success. In addition, effective communication between the school and parents is also influential in monitoring students' learning progress and providing solutions to the obstacles faced.